Language and literacy in inquiry-based science classrooms, grades 3-8 - Fang, Zhihui; Lamme, Linda Leonard; Pringle, Rose M.; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE [distributor], 2010)
Research has long supported the positive effects of integrating literacy practices into the science curriculum; now this helpful and timely resource offers science educators effective strategies that they can implement immediately.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Science -- Study and teaching (Elementary); Science -- Terminology -- Study and teaching (Elementary); Language arts -- Correlation with content subjects; Electronic books